Exploring cardiovascular disease prevalence and contributing factors among adults in Southern Iran, a cross-sectional survey: Rationale, design, and primary results - Hossein Farshidi; Marzieh Nikparvar; Shokrollah Mohseni; Ebrahim Eftekhar; Farideh Dastsouz; Abdoljabbar Zakeri; Mohammad Mohammadi; Farkhondeh Razmpour; Farid Khorrami; Masoumeh Mahmoodi; Nahid Shahabi; Soghra Fallahi; et al. (PLoS ONE, 2025)
Background and objectives Cardiovascular disease (CVD) is the primary cause of death worldwide, with significant fatalities reported in Iran. Hormozgan Province in southern Iran faces serious public health challenges related to CVD, a major cause of morbidity and mortality in the region. This study investigates the prevalence of CVD and its contributing factors in this region. Method This cross-sectional study was conducted in Hormozgan Province, southern Iran, from June 21 to December 21, 2023. A total of 6289 individuals aged 20 and older were selected through random multistage sampling techniques. Data collection involved three phases: administering a comprehensive questionnaire, measuring anthropometric data and blood pressure, and conducting laboratory blood tests. CVD was defined as the presence of ischemic heart disease (IHD) or ischemic and hemorrhagic strokes. Data analysis was performed using SPSS version 26, incorporating statistical tests such as multivariable logistic regression, Mann-Whitney tests, and Chi-square to compare groups. Results A total of 6289 participants were included in the study, with a mean age of 45.63 ± 15.04 years. Among them, 58.5% were female, and 51.6% lived in urban areas. Key findings revealed that 45.7% of the population were identified as overweight or obese, with a significant prevalence of abdominal obesity at 69.6%, particularly among females. The prevalence of CVD in the population was 7.8%, with IHD affecting 6.7% of individuals and stroke affecting 2.2%. Multivariable logistic regression identified increased age (AOR: 1.03; 95% CI: 1.02–1.04), higher body mass index (BMI) (AOR: 1.02; 95% CI: 1.00–1.05), hypercholesterolemia (AOR: 1.30; 95% CI: 1.03–1.66), hypertension (HTN) (AOR: 2.02; 95% CI: 1.55–2.64), diabetes (AOR: 1.31; 95% CI: 1.00–1.71), and severe anxiety (AOR: 2.39; 95% CI: 1.30–4.39) as significant risk factors for CVD. Women had a 33% lower risk of having CVD compared to men (AOR: 0.67; 95% CI: 0.53–0.85). Conclusion This study highlights urgent public health concerns in Hormozgan Province, including high rates of CVD, obesity, abnormal blood pressure, and diabetes, particularly among females, underlining the need for targeted health interventions and improved nutritional practices.